Manajemen Strategi Pelayanan SERVQUAL Ibadah Umrah Pada Jemaah Disabilitas Fisik PT. Harum Bina Wisata, Indramayu - Faizah, Auliatul; Muhajarah, Kurnia; Affandi, Yuyun; Anasom, Anasom; Rozaq, Abdul; Sattar, Abdul (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the management of SERVQUAL service strategies in Umrah worship for physically disabled pilgrims at PT. Harum Bina Wisata, Indramayu. To ensure that physically disabled pilgrims can perform Umrah worship smoothly and solemnly, PT. Harum Bina Wisata has developed a special strategy that focuses on meeting the needs of pilgrims with physical disabilities. The methodology used in this study is descriptive qualitative, which is based on field analysis. Data were collected through direct observation, interviews with (managers, staff of PT. Harum Bina Wisata, and physically disabled pilgrims), and documentation which was then analyzed thematically to evaluate the effectiveness of the implementation of the five dimensions of SERVQUAL: tangible, reliability, responsiveness, assurance, and empathy. The results of the study indicate that the main strength of the bureau lies in its experience and deep understanding of the needs of physically disabled pilgrims. The tangible dimension is reflected in disability-friendly facilities, such as wheelchairs, hotel accessibility, and safe and comfortable transportation. The reliability and assurance dimensions are seen in the consistency of service and the ability of staff to ensure the safety and comfort of pilgrims during the trip. Responsiveness is demonstrated through the bureau's ability to respond to sudden needs, while empathy is seen in a personal approach that fosters a sense of appreciation among pilgrims. Although the results show quite high satisfaction, a significant challenge faced is the limited number of workers with special skills in serving pilgrims with physical disabilities. Therefore, it is recommended to develop special training for staff, improve the quality and quantity of facilities, and collaborate with disability organizations to improve the quality of service. This study is expected to provide a significant contribution in creating a more inclusive and quality Umrah service for pilgrims with physical disabilities at PT. Harum Bina Wisata.